48. EARLY BREASTFEEDING INITIATION AMONG WOMEN IN LAO PDR: A QUALITATIVE STUDY ON THE CHALLENGES OF IN A HOSPITAL-BASED INTERVENTION (Tạp chí Y học Cộng đồng, 2024)
Background: Early initiation of breastfeeding within the first hour of life occurred in about only 39.6% of Laotian infants. This study is to assess the challenges of a hospital-based intervention supporting early initiation of breastfeeding among postpartum women in Bokeo Provinical hospital during 2022-2023.Materials and Method: A descriptive qualitative study on health providers and postpartum women in Bokeo Provinical hospital was conducted. A total of 12 participants were involved in the study (1 focus group discussion with 7 health providers and 5 in-depth interviews with postpartum mothers and their relatives). All qualitative data were thematically analysed using Microsoft Word.Result: The following themes were found: 1) Further support for early initiation of breastfeeding, 2) Shortage of exclusively breastfeeding follow-up, and 3) Shortage of feasible solutions. There was an emphasis on early initiation of breastfeeding, which was challenged by maternal exhaustion after delivery. Study participants reported poor follow-up on breastfeeding practice after initial counselling and reacting to adverse outcomes in lieu of adequate monitoring, with a reliance on mothers to follow-up on challenges. There was poor support for facility-based breastfeeding after initial counselling post-delivery, which revealed an overall neglect in hospital postpartum care for those considered to be in good health after initial assessment.Conclusion: This study provides insight for further understanding of the challenges for an intervention on early breastfeeding initiation for women in Lao PDR.  We recommend the development of indicators to track continued facility-based breastfeeding, identify vulnerable infants at-risk of feeding problems, and strengthening care in postnatal wards, which is currently as neglected component of maternity care.Background: Early initiation of breastfeeding within the first hour of life occurred in about only 39.6% of Laotian infants. This study is to assess the challenges of a hospital-based intervention supporting early initiation of breastfeeding among postpartum women in Bokeo Provinical hospital during 2022-2023.Materials and Method: A descriptive qualitative study on health providers and postpartum women in Bokeo Provinical hospital was conducted. A total of 12 participants were involved in the study (1 focus group discussion with 7 health providers and 5 in-depth interviews with postpartum mothers and their relatives). All qualitative data were thematically analysed using Microsoft Word.Result: The following themes were found: 1) Further support for early initiation of breastfeeding, 2) Shortage of exclusively breastfeeding follow-up, and 3) Shortage of feasible solutions. There was an emphasis on early initiation of breastfeeding, which was challenged by maternal exhaustion after delivery. Study participants reported poor follow-up on breastfeeding practice after initial counselling and reacting to adverse outcomes in lieu of adequate monitoring, with a reliance on mothers to follow-up on challenges. There was poor support for facility-based breastfeeding after initial counselling post-delivery, which revealed an overall neglect in hospital postpartum care for those considered to be in good health after initial assessment.Conclusion: This study provides insight for further understanding of the challenges for an intervention on early breastfeeding initiation for women in Lao PDR.  We recommend the development of indicators to track continued facility-based breastfeeding, identify vulnerable infants at-risk of feeding problems, and strengthening care in postnatal wards, which is currently as neglected component of maternity care.
Keywords: early initiation of breastfeeding; maternal and child health care; qualitative study; hospital-based intervention; Lao PDR